Let's go West!: Do East Germans commute for wages, jobs or skills? - Jörn-Steffen Pischke; Matthias Staat; Stefan Vögele (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1993)
Using data from the longitudinal Labor Market Monitor for the New German States we provide a portrait of East-West commuters in the first year after unification and evaluate various hypotheses to explain the phenomenon. Commuters may be driven by the search for higher wages in the west or by unemployment in the east. Comparing commuters and other job starters in the east with respect to their previous labor force status we find the unemployed and those fearing job loss in the future to be less likely to hold jobs in the west. While many commuters realize significant wage gains some do not. We examine whether these commuters are likely to be acquiring additional human capital through employer provided training. While the incidence and duration of training is high among commuters, wage gains for those without training are lower. This leaves the wage differential hypothesis as the most likely explanation for the commuting phenomenon.
Keywords: 330; Berufsverkehr; Neue Bundesländer; Deutschland